Migration Processes in the Post-Soviet Space: Russia and the Peculi - M. A. Burda (Проблемы постсоветского пространства, 2023)
The article considers migration processes in the post-Soviet space, relative to the Russian Federation, as the main center of migration attraction. Empirical data are introduced into scientific circulation, characterizing some migration indicators in 2022 on the basis of which the features of external labor migration to Russia are revealed. The author analyzes quantitative and qualitative indicators of external migration on the basis of not only statistical data, but also regulatory legal acts, which makes it possible to determine the ratio of migration needs and migration challenges faced by Russian society, which generally negatively perceives the migration model implemented in the state. The conclusion proposes measures that allow, according to the author, to increase the effectiveness of the implemented state migration policy and reduce the conflict potential of external migration.